Hayek and Rawls’s theories of justice: divergences and convergences beyond mere terminology - de Quadros, Matheus (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The present article aims to compare the theories of justice proposed by Friedrich Hayek and John Rawls, attempting to analyze Hayek´s curious assertion that the difference between authors would be more on terminology than content. To do this, it will verify indirect bibliographic documentation as a way of understanding the convergences and divergences between the authors, tracing the general concepts of both theories and aiming at the ideological parallels of both authors. The article concludes that the authors, although liberals who have relied on similar sources in their formation, arrive at completely different conclusions in their theories of justice, which is explained by diverse conceptual notions and theoretical ends between the authors, despite several methodological convergences that motivated Hayek’s assertion in the first place.